A Grammar for Representing Uniform Local Binary Patterns (ULBP) - Vijaya Kumar, Vakulabharanam; Murthy. G, Vishnu; Obulesu, A. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
One of the recently invented theoretically simple and efficient operators that is playing a significant role in image processing, pattern recognition and other domains is the Local Binary Pattern (LBP). LBP measures the local texture features on a given neighbourhood efficiently. The Uniform LBP (ULBP) that is derived on LBP is treated as the fundamental unit of the textures. There 58 ULBPs out of 256 LBPs on a 3 x3 neighbourhood. Further the textures on average contain 75% to 90% of the patterns as ULBP only. One disadvantage is representing all 58 ULBS. To say whether a given LBP is uniform or not one should march the given LBP with 58 Patterns. Very few research scholars derived grammar to represent patterns that arises from 2-D images. The present paper addresses the above problem by generating a simple array grammar that represents all ULBP on a 3 x 3 neighbourhood or with 8 neighbours.The present paper tests the proposed Array Grammar model of ULBP (AG-ULBP) with various LBP patterns to prove its accuracy.